Does Prematch Neuromuscular Performance Affect Running Performance in Collegiate Elite Female Soccer?. Issue 4 (18th April 2023) - Ishida, Ai; Draper, Garrison; White, Jason B.; Travis, S. Kyle
Abstract: Ishida, A, Draper, G, White, JB, and Travis, SK. Does prematch neuromuscular performance affect running performance in collegiate elite female soccer? J Strength Cond Res 37(4): 854–858, 2023—The purpose of this study was to investigate whether prematch neuromuscular performance affected match physical performance by player position in Division I collegiate female soccer. Fourteen players participated (20.7 ± 1.3 years; 165.1 ± 6.0 cm; 63.3 ± 7.0 kg) in this study. Players were selected based on being free from injuries, playing for a duration of ≥72 minutes, and match intervals were ≥2 days. Data included 73 observations ( n = 5 defenders, n = 7 midfielders, and n = 2 forward) from 14 official matches. Prematch neuromuscular performance was assessed using countermovement jump (CMJ) with polyvinyl chloride pipe on dual force plates. Countermovement jump variables included jump height (JH) and relative peak power (RPP). Match physical performance included average speed, high-speed running (HSR), and number of high accelerations and decelerations. Linear mixed model was compiled with fixed effects of loaded with fixed effect of JH, RPP, and position and random effects per individual player. In CMJ and player position model, RPP was a significant predictor for average HSR ( p = 0.003) while fixed effects of JH and position were not significant ( p = 0.15–0.86). The fixed and random effects explained 34.8 and 42.1% of variances in average HSR. In CMJ-only model, RPP significantly predicted the variances in average HSR ( p = 0.001). The fixed effects and random effects of the model explained 22.7 and 51.8% of the variance in average HSR. However, position-only was not a significant predictor for average HSR in the position-only model ( p = 0.26 and 0.33). Prematch CMJ RPP may be the greatest predictor of average HSR in collegiate female soccer.